Perbedaan kontrol diri siswa dalam penggunaan smartphone ditinjau dari jenis kelamin - Afla Khairani; Indah Sukmawati (Counseling and Humanities Review, 2023)
This study aims to analyze differences in students' self-control in using smartphones in terms of gender. This research uses a quantitative method with a comparative descriptive research type. The population of this study was 969 students at SMAN 4 Payakumbuh with a sample of 287 students. The sample was taken using a stratified random sampling technique. The instrument used was a "self-control research instrument" using a Likert model scale. Data were analyzed using descriptive statistical techniques and independent sample t-test techniques. The research findings show that: 1) Male students' self-control in using smartphones is in the moderate category, 2) Female students' self-control in using smartphones is in the moderate category, and 3) there is a significant difference between students' self-control in using smartphones in terms of gender with a significant value of 0.027 < 0.05, meaning that there is a significant difference between male students' self-control and female students' self-control in using smartphones, which means Ha is accepted. Based on the results of the research that has been done, the results obtained are that there is a significant difference between male and female students' self-control in using smartphones.